2022
DOI: 10.3389/fneur.2022.719208
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment Early After Initiating Maintenance Hemodialysis: A Cross Sectional Study

Abstract: BackgroundAbnormalities in cognitive function are almost universal in patients receiving hemodialysis (HD) and are associated with worse quality of life, impaired decision making, increased healthcare utilization and mortality. While cognitive impairment in the HD population is increasingly recognized, it is unclear how quickly it develops after starting HD.MethodsThis was a cross-sectional study of a cohort of low dialysis vintage HD patients (<12 months). We used the validated Cambridge Brain Science … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
1
0
0
Order By: Relevance
“…conventional treatment, HD and peritoneal dialysis) or the severity of the disease. Melissa et al [39] found that patients undergoing HD are more vulnerable to damage to their visual-spatial processing, deductive reasoning, executing, and verbal skills than their short-term memory, and these ndings support our speculation; however, a study with a larger sample size will be required to validate our ndings. Nevertheless, our discovery of FC regions in the right MFG may provide additional brain imaging markers for cognitive impairment in patients with ESHD.…”
Section: Discussionsupporting
confidence: 84%
“…conventional treatment, HD and peritoneal dialysis) or the severity of the disease. Melissa et al [39] found that patients undergoing HD are more vulnerable to damage to their visual-spatial processing, deductive reasoning, executing, and verbal skills than their short-term memory, and these ndings support our speculation; however, a study with a larger sample size will be required to validate our ndings. Nevertheless, our discovery of FC regions in the right MFG may provide additional brain imaging markers for cognitive impairment in patients with ESHD.…”
Section: Discussionsupporting
confidence: 84%
“…Consequently, HD patients are more likely than the general population to have white matter hyperintensities on magnetic resonance imaging (MRI), a marker for small-vessel ischemic disease, and are therefore at higher risk for future stroke or cognitive decline [4,5]. It is known that HD patients are at increased risk of developing cognitive problems such as mild cognitive impairment (MCI), i.e., mild, noticeable deterioration of cognitive functions, and dementia [6][7][8]. Up to 80% of HD patients aged 55 and older have been shown to have moderate to severe chronic cognitive impairment (CI) [6,7].…”
Section: Introductionmentioning
confidence: 99%